Drivers of Employee Engagement in Global Virtual Teams - Shaik, Farheen Fathima; Makhecha, Upam Pushpak (Australasian Journal of Information Systems, 2019)
Global Virtual Teams (GVTs) comprise geographically distributed groups of people collaborating with each other through technology-mediated communication. Members of GVTs are from different cultural backgrounds and time zones, who may (or may not) meet in person to take complex decisions or to deliver on the tasks that are of strategic importance. Though technology has enabled GVTs in almost all multinational organisations across all industries, keeping the members of GVTs engaged over the duration of the team’s task or project could still pose a challenge for organisations. Employee engagement is defined as an employee’s cognitive, behavioural and physical state directed towards organisational outcomes. While employee engagement has been researched in a collocated team context, it remains an under-researched area in the context of GVTs. Given that there are several characteristics of GVTs which are distinct from the collocated team, it warrants a separate inquiry, which we undertake in this study. This study uses the Job Demands-Resources theory of employee engagement to derive the drivers of employee engagement in GVTs. Through interpretive analysis of the lived experiences of members working in an organisation which extensively uses GVTs for achieving its strategic goals, we conceptualise five drivers of employee engagement, namely, cultural intelligence, communication (formal and informal), technology, trust and individual maturity.